The effect of industrial waste on air pollution and water pollution causes climate change - Ditia, Syifa (Journal of Waste and Sustainable Consumption, 2024)
Background: Industrial pollution refers to any type of contamination that results directly from industrial operations. The majority of the pollution on this planet is also caused by various industries. The environment is greatly impacted by this pollution. Industrial pollution can degrade soil quality, taint sources of drinking water, and emit pollutants into the atmosphere. Energy and industrial pollution are intimately intertwined. Energy can transform from one form to another, and these changes can have a variety of effects on the surrounding area and the air we breathe. The main source of pollution is combustion, which transforms the chemical energy in fossil fuels into heat, mechanical, or electrical energy. So the biggest sources of air pollution are power plants, cars, and stoves. The pollutants released are often divided into three categories: carbon monoxide (CO), nitrogen oxides (NOx), and hydrocarbons (HC) (CO). Smog, acid rain, global warming, and climate change are mostly caused by pollutants released by the burning of fossil fuels. Future life is impacted by climate change. Deforestation, or the loss of green forest ecosystems, is one of the causes of global warming. This is because it ignores the consequences of industrial opening and changes in land use brought on by population increase. Environmental issues including air pollution and water pollution are significantly impacted by pollutants produced by the industrial sector. This research explains the effect of industrial waste on air pollution and water pollution. Methods: The research method used is a secondary method, namely research that involves the use of existing data. The sources in this study were taken from journals related to the effect of industrial waste on air pollution and water pollution which are one of the causes of climate change. Findings: At both the national and international levels, legislation and regulations have been implemented that take this environmental concern into consideration. Conclusion: The issue of climate change is related to reducing greenhouse gas (CO2) emissions at the international level, for instance in the energy sector. This is done within the framework of the United Nations, specifically the Climate Change Convention outlined in the Kyoto Protocol, which requires ratifying countries to reduce CO2 emissions to an agreed-upon target.